Fire prevention measures (Czech Journal of Multidisciplinary Innovations, 2022)
This article describes measures to prevent fires, the process of combustion, types of combustion, categories of industrial enterprises on fire and explosion hazard, fire safety when working with electrical appliances, the organization of firefighting services